Strategi Bela Negara untuk Meningkatkan Ketahanan Nasional di Era Globalisasi - Eka, Eka; Kurniati, Kurniati; Faujiah, Zaitun; Nurhasanah, Nurhasanah (Indo-MathEdu Intellectuals Journal, 2024)
Pancasila is often seen as an ideology that deals with global ideologies, such as capitalism and liberalism. The Pancasila that was built is for common welfare and social justice for all Indonesian people. This article aims to find out the national defense strategies that can be carried out to increase national resilience in the era of globalization. This research uses a qualitative approach through the literature study method. The main source of this research data is the research article published through google scholar. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. Based on the results of data analysis, it can be concluded that the dynamic implementation of Pancasila values in the life of society, nation, and state so that Pancasila remains relevant in its function as a guideline for decision-making and problem-solving in the life of the nation and state, and so that the loyalty of citizens and citizens to Pancasila is maintained. In the era of globalization, the strategy of defending the country is very important to increase national resilience. Therefore, governments, communities, and non-governmental organizations must work together to create effective national defense strategies to ensure national security and resilience and increase public awareness of the importance of national defense to enhance national resilience